2022
DOI: 10.1097/ju.0000000000002910
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Intrarectal Povidone-iodine Cleansing Plus Formalin Disinfection of the Needle Tip in Decreasing Infectious Complications After Transrectal Prostate Biopsy: A Randomized Controlled Trial

Abstract: Purpose:Prostate biopsy is mostly performed through the transrectal route worldwide and infectious complications may occur in up to 7% of cases. Therefore, alternative strategies to decrease infectious complications are needed. Our aim was to evaluate the effectiveness of intrarectal povidone-iodine cleansing plus formalin disinfection of the needle tip in decreasing infectious complications after transrectal ultrasound guided prostate biopsy.Materials and Methods:We conducted a prospective, single-center, pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…However, TRUS-Bx leads to higher incidence of infectious complications based on the translocation of rectal bacteria during the procedure. The estimated incidence rate of infectious complications by TRUS-PB, such as acute bacterial prostatitis, fever, and sepsis, is reported to be as high as 6.3% [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, TRUS-Bx leads to higher incidence of infectious complications based on the translocation of rectal bacteria during the procedure. The estimated incidence rate of infectious complications by TRUS-PB, such as acute bacterial prostatitis, fever, and sepsis, is reported to be as high as 6.3% [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies, including randomized controlled trials (RCT), have been conducted to assess the efficacy of PI disinfection of the rectum in reducing infectious complications after TRUS-PB [ 2 , 4 9 ]. These studies have indicated that PI disinfection can reduce infectious complications, leading to the EAU guidelines to recommend rectal disinfection with PI prior to TRUS-PB [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…This single-center RCT randomized 1234 patients undergoing TRUS-Bx to receive preprocedure rectal cleansing with 10% povidone-iodine and used a formalin-dipped needle in the intervention arm. [ 23 ] Both the treatment groups received 3 days of ciprofloxacin starting one night before. Infectious complications in terms of fever, UTI, or sepsis were significantly decreased in the intervention arm (3.9% vs. 6.4%, P = 0.49).…”
Section: Effectiveness Of Intrarectal Povidone-iodine Cleansing Plus ...mentioning
confidence: 99%
“…Pontes Junior et al (page 1194) from Brazil report a randomized single center study looking at rectal cleaning with a gauze soaked in 10% povidone-iodine while the patient is positioned, and cleaning the needle tip with formalin before each puncture. 3 The authors are to be commended in randomizing 1,256 patients. They found a decrease in positive urine cultures and a difference in overall infectious complications: 3.9% in the intervention group and 6.4% in controls.…”
Section: A Simple Modification Of Transrectal Prostate Biopsy To Redu...mentioning
confidence: 99%